Between rights and reality: patient perceptions of social inclusion in a forensic psychiatric clinic implementing safewards - Pelto-Piri, Veikko; Kjellin, Lars; Kronman, Linn; Wetterling, Jenny; Björkdahl, Anna (Frontiers in Psychiatry, 2025)
BackgroundUpholding human rights, including promoting patients’ social inclusion, is essential in forensic psychiatric services to ensure socially sustainable development. Understanding how social inclusion it is perceived by patients is therefore important. Evidence suggests that the Safewards model can enhance social inclusion in inpatient settings. The aim of this study was to explore patients’ perceptions of social inclusion in a forensic psychiatric clinic that implemented the Safewards model. To provide context, a secondary aim was to describe which Safewards interventions were implemented and how patients perceived them.MethodsEight male patients from a forensic psychiatric clinic in Sweden were individually interviewed, focusing on Safewards and opportunities for social inclusion. Thematic content analysis was used to deductively code the data under the three core values of a social inclusion model: participation in decision-making, reciprocal relationships, and social justice. Themes for each value were thereafter developed inductively. For the secondary aim, a concise qualitative description was used to create an overview of patients’ perceptions of Safewards.ResultsPatients were aware of the Safewards interventions and were generally positive about them. Nine themes emerged: powerlessness when meeting the doctor; limited experience of involvement in daily decisions; desire to become involved in quality improvement efforts (participation in decision-making); staff members’ availability and positive attitude; fellow patients exhibit care and consideration; withdrawal and avoidance of social interaction (reciprocal relationships); boredom and low mood within the ward; desire for dignified, equal, and safe care; and perception of unjustified confinement (social justice).ConclusionThe findings suggest that while Safewards may support more compassionate staff–patient relationships, it does not in itself ensure participatory or rights-based care. Achieving higher levels of social inclusion in forensic psychiatric services requires broader cultural and structural reforms beyond the implementation of individual models.